Social Movements and Their Impact on Democratic Transition - Mohammed Misbah Elelam (Journal of Scientific and Human Dimensions, 2025)
Social movements represent one of the most prominent non-traditional actors in contemporary political life. In recent decades, they have become an undeniable force in shaping political and social transformations across the globe. With the escalation of economic and political crises and the obstruction of official channels of participation, social movements have emerged as an alternative framework for expressing popular aspirations and a pressure platform that reshapes the relationship between the state and society. They contribute to the redistribution of roles within the political system, particularly in societies undergoing a transition to democracy. International experience has shown that democratic transition is a complex and protracted process involving intertwined political, economic, and cultural factors, not merely a formal shift from an authoritarian to a democratic system of governance. At the heart of this process, social movements serve as a key instrument for popular mobilization, a means of political pressure, and an incubator for a culture of participation and democratic awareness. Social movements express the will of broad segments of citizens seeking to rectify the imbalances of the political system and achieve fundamental reforms that guarantee respect for rights and freedoms and strengthen the rule of law
Keywords: Social movements; Political life; Economic and political crises; State and society; Popular mobilization